2008
DOI: 10.1111/j.1525-142x.2008.00280.x
|View full text |Cite
|
Sign up to set email alerts
|

Platypus Pou5f1 reveals the first steps in the evolution of trophectoderm differentiation and pluripotency in mammals

Abstract: Uterine nourishment of embryos by the placenta is a key feature of mammals. Although a variety of placenta types exist, they are all derived from the trophectoderm (TE) cell layer of the developing embryo. Egg-laying mammals (platypus and echidnas) are distinguished by a very short intrauterine embryo development, in which a simple placenta forms from TE-like cells. The Pou5f1 gene encodes a class V POU family transcription factor Oct3/4. In mice, Oct3/4 together with the highly conserved caudal-related homeob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(68 citation statements)
references
References 53 publications
2
66
0
Order By: Relevance
“…Due to the deficiency of sequence information for the primitive fish, the exact time when pou5f1 appeared in the evolutionary tree was uncertain. Niwa et al (2008) suggested that pou5f1 and pou2 genes are paralogs and arise by gene duplication in primitive mammalian evolution. However, as it was credibly shown by Frankenberg et al (2010), the duplication of pou5f1 and pou2 occurred at least in the early tetrapod lineage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Due to the deficiency of sequence information for the primitive fish, the exact time when pou5f1 appeared in the evolutionary tree was uncertain. Niwa et al (2008) suggested that pou5f1 and pou2 genes are paralogs and arise by gene duplication in primitive mammalian evolution. However, as it was credibly shown by Frankenberg et al (2010), the duplication of pou5f1 and pou2 occurred at least in the early tetrapod lineage.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, there were differences in the linker, such as the length of a-helix and the number of the turn and b-sheet, which might be the reason for their divergence of functions. For instance, result from some differences of POU domain sequence, self-renewal function of the class V POU domain transcription factors was affected (Niwa et al 2008). Due to the deficiency of sequence information for the primitive fish, the exact time when pou5f1 appeared in the evolutionary tree was uncertain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18,21,22 However, recent reports claim that in the early vertebrate lineage the Pou5 class was represented by a single gene, which was duplicated before the mammalian radiation to give rise to the two Pou5 genes found today in noneutherian mammals. 35,36 One copy was subsequently lost in eutherian mammals, resulting in the single Oct4 gene present in mouse and humans. Therefore the pluripotency gene Oct4 is not the ortholog of chicken Pou2-related (Pou2-r, following the nomenclature of Niwa 36 ) and other vertebrate Pou5 genes, but a paralog.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…35,36 One copy was subsequently lost in eutherian mammals, resulting in the single Oct4 gene present in mouse and humans. Therefore the pluripotency gene Oct4 is not the ortholog of chicken Pou2-related (Pou2-r, following the nomenclature of Niwa 36 ) and other vertebrate Pou5 genes, but a paralog. The frequently result from local or global duplication events.…”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%